Determinants of infarct progression and perfusion core growth in transferred LVO patients from remote regions - Valente, Michael; Bivard, Andrew; Yan, Bernard; Davis, Stephen M.; Campbell, Bruce C. V.; Mitchell, Peter J.; Ma, Henry; Parsons, Mark W. (Frontiers in Neurology, 2024)
Introduction Repeat imaging when regional and remote stroke patients arrive at a comprehensive stroke center (CSC) can delay endovascular thrombectomy (EVT). We examined which clinical and imaging parameters predict infarct progression and perfusion core growth during transport. Methods We included patients recruited from 2017 to 2023 in a prospective database who were transferred from remote sites with large vessel occlusion, had CT perfusion imaging at the primary stroke center (PSC), and had repeat CT on arrival at the CSC demonstrating persistent occlusion. The key imaging characteristics were perfusion core change (rCBF < 30%) and ASPECTS change. Multiple and ordinal logistic regression analyses were used to assess the relationship between background clinical and imaging variables and the CT-perfusion core and ASPECTS on arrival. DEFUSE 3 criteria (ASPECTS ≥ 6, perfusion core < 70 mL) were used to define “favorable imaging.” Results In 90 patients with CT perfusion at both PSC and CSC and persistent occlusion, the median time from onset to PSC presentation was 279 min (IQR 143–702). The median time from PSC presentation to CSC arrival was 243.5 min (IQR 186–335), and the median distance traveled was 186.5 km (IQR 101–258). Lower baseline ASPECTS (per point) was associated with a 7 mL increase (95%CI 2–11 mL) in perfusion core between scans (p = 0.004). The time from onset, the time between PSC and CSC, and the distance traveled were not significantly associated with either ASPECTS or perfusion core growth during transport. In total, 11 out of 78 patients (14%) had deterioration of initially favorable imaging profiles during transport. Conclusion Perfusion core growth during transport was uncommon and most strongly associated with lower ASPECTS at the PSC. Initially, favorable PSC imaging May predict whether repeat imaging is necessary at the CSC.